Oligolysine-based coating protects DNA nanostructures from low-salt denaturation and nuclease degradation - Ponnuswamy, Nandhini; Bastings, Maartje M. C.; Nathwani, Bhavik; Ryu, Ju Hee; Chou, Leo Y. T.; Vinther, Mathias; Li, Weiwei Aileen; Anastassacos, Frances M.; Mooney, David J.; Shih, William M. (Nature Publishing Group, 2017)
DNA nanostructures have evoked great interest as potential therapeutics and diagnostics due to ease and robustness of programming their shapes, site-specific functionalizations and responsive behaviours. However, their utility in biological fluids can be compromised through denaturation induced by physiological salt concentrations and degradation mediated by nucleases. Here we demonstrate that DNA nanostructures coated by oligolysines to 0.5: 1 N:P (ratio of nitrogen in lysine to phosphorus in DNA), are stable in low salt and up to tenfold more resistant to DNase I digestion than when uncoated. Higher N: P ratios can lead to aggregation, but this can be circumvented by coating instead with an oligolysine-PEG copolymer, enabling up to a 1,000-fold protection against digestion by serum nucleases. Oligolysine-PEG-stabilized DNA nanostructures survive uptake into endosomal compartments and, in a mouse model, exhibit a modest increase in pharmacokinetic bioavailability. Thus, oligolysine-PEG is a one-step, structure-independent approach that provides low-cost and effective protection of DNA nanostructures for in vivo applications.